EKSPLORASI KETERAMPILAN MATEMATIKA YANG MEMPENGARUHI KEMAMPUAN NUMERASI SISWA SEKOLAH DASAR - Nanna, A Wilda Indra; Pratiwi, Enditiyas (Prodi Pendidikan Matematika FKIP Universitas Madura, 2025)
This study aims to explore the skills that students need to develop in order to utilize mathematical knowledge in solving numeracy problems. A descriptive qualitative approach was employed, utilizing test instruments and in-depth interviews for data collection. Twenty-one fifth-grade elementary students participated in the numeracy assessment, with three subjects—representing low, medium, and high numeracy proficiency—selected for detailed interviews. Findings reveal that only students with high numeracy competence demonstrated the ability to integrate number sense, an understanding of mathematical relationships, computational skills, and information interpretation to solve numeracy tasks successfully. Conversely, students with medium and low proficiency exhibited significant difficulties, particularly in comprehending problem contexts and accurately applying arithmetic operations. Therefore, numeracy learning strategies need to integrate the strengthening of mathematical literacy and the development of conceptual understanding.